2021
DOI: 10.3390/v13020352
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus (RSV) G Protein Vaccines With Central Conserved Domain Mutations Induce CX3C-CX3CR1 Blocking Antibodies

Abstract: Respiratory syncytial virus (RSV) infection can cause bronchiolitis, pneumonia, morbidity, and some mortality, primarily in infants and the elderly, for which no vaccine is available. The RSV attachment (G) protein contains a central conserved domain (CCD) with a CX3C motif implicated in the induction of protective antibodies, thus vaccine candidates containing the G protein are of interest. This study determined if mutations in the G protein CCD would mediate immunogenicity while inducing G protein CX3C-CX3CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 87 publications
2
33
1
Order By: Relevance
“…Moreover, several neutralising and protective antibodies have been isolated that target the CCD within RSV G [29][30][31][32]. Immunisation of mice with RSV G immunogens has also been shown to elicit antibodies capable of blocking the interaction of G with CX3CR1 [72], providing a rationale for inclusion of the CCD in vaccine designs. In this study, we extended the FxG strategy from NiV (Paramyxoviridae) to phylogenetically distinct RSV (Pneumoviridae).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several neutralising and protective antibodies have been isolated that target the CCD within RSV G [29][30][31][32]. Immunisation of mice with RSV G immunogens has also been shown to elicit antibodies capable of blocking the interaction of G with CX3CR1 [72], providing a rationale for inclusion of the CCD in vaccine designs. In this study, we extended the FxG strategy from NiV (Paramyxoviridae) to phylogenetically distinct RSV (Pneumoviridae).…”
Section: Discussionmentioning
confidence: 99%
“…To determine if probenecid treatment affected the anti-RSV antibody response, the sera from four female mice per group collected at days 7 pi were diluted (1:40) and assayed by ELISA using a modi ed protocol as described 44 . The ELISA detects both neutralizing and non-neutralizing antibodies and the use of RSV A2 lysate antigen provides a way to detect antibodies against multiple RSV proteins.…”
Section: Methodsmentioning
confidence: 99%
“…Accumulating evidence has shown the protective benefits of G protein-mediated antibodies specifically regarding disease pathogenesis, thus G protein-based vaccines are being reconsidered [220]. Studies in mice have suggested that modification of the CX3C motif [221,222] and/or CCD [223] could elicit a safe and protective response and shift Th2-type responses to Th1-type or balanced responses. A G protein DNA vaccine (pVAX1/3G ) was shown to induce a Th1-type biased response and protect mice from the disease [224].…”
Section: Cd4+ T Cellsmentioning
confidence: 99%